A new U-Pb age for shock-recrystallised zircon from the Lappajärvi impact crater, Finland, and implications for the accurate dating of impact events - Kenny, G.; Schmieder, M.; Whitehouse, M.; Nemchin, Alexander; Morales, L.; Buchner, E.; Bellucci, J.; Snape, J. (Pergamon, 2019)
Accurate and precise dating of terrestrial impact craters is a critical requirement for correlating impacts with events such as mass extinctions. A number of isotopic systems have been applied to impact chronology but it is important to understand what an age actually represents and, thus, if it accurately represents the ‘true’ impact age and is suitable for use in correlation. Here we report imaging, microstructural characterisation and high spatial resolution ion microprobe U-Pb analysis of shocked zircon from the approximately 23 km-in-diameter Lappajärvi impact structure, Finland, for which a well-established 40Ar/39Ar framework exists. Microstructural analysis identified two distinct styles of shock recrystallisation: (i) granular zircon that displays multiple domains of similarly oriented neoblasts, some of which are interpreted to be the product of reversion from the high-pressure ZrSiO4 polymorph, reidite, and (ii) granular zircon composed entirely of similarly oriented neoblasts. Only the former gave concordant U-Pb data interpreted to record the age of the impact. The U-Pb ‘concordia age’ reported here, 77.85 ± 0.78 Ma (1.0%; MSWD = 0.60; probability = 0.87; n = 8; 2s; full external uncertainty), is resolvable from the previously published ‘best estimate’ 40Ar/39Ar age for impact melt rock (76.20 ± 0.29 Ma) and 40Ar/39Ar K-feldspar ages as young as 75.11 ± 0.36 Ma, and is therefore interpreted to more accurately reflect the age of the impact event. The resolvable disparity between the zircon U-Pb and the 40Ar/39Ar data indicates that even the oldest statistically robust 40Ar/39Ar ages obtained at medium- and large-sized impact craters may not accurately record the timing of an impact event at a kyr level. The offset between the U-Pb and 40Ar/39Ar data is interpreted to be, at least in part, a result of the zircon data recording a higher isotopic closure temperature, and the younger 40Ar/39Ar ages recording the progressive cooling of different domains of the impact structure. The Lappajärvi impact structure is the first Phanerozoic impact structure dated by U-Pb analysis of shock-recrystallised zircon to better than, or equal to, 1.0% uncertainty. This further demonstrates that well-characterised granular zircon grains are likely to have wide utility in the accurate and precise dating of terrestrial impact events.